Development of Static Fluid Teaching Materials Containing Quranic Verses to Improve Student Learning Outcomes - Nurliana Nurliana; Zainuddin Zainuddin; Mastuang Mastuang (Jurnal Ilmiah Pendidikan Fisika, 2025)
The preliminary observation results revealed the limited availability of teaching materials that incorporate spiritual aspects, particularly the Quran. This study aims to describe the instructional material development process and analyze the suitability of the instructional material in enhancing students' learning outcomes, based on validity, practicality, and effectiveness. The study was conducted with students of Class XI MIPA 1 at MAN 1 Banjarmasin, utilizing the ADDIE model. Data were collected from the results of validating teaching materials using the lesson plan implementation sheet, as well as student learning outcomes in the pre-test and post-test. The results of this study indicate that the developed teaching materials have a validity level categorized as valid, a practical level of teaching materials categorized as practical, and a level of effectiveness categorized as effective or moderate, with an N-gain value of 0.69. This study found that the teaching materials for static fluid materials with Al-Qur'an verses to improve student learning outcomes are declared suitable for use based on the validity, practicality, and effectiveness of the teaching materials.